2006
DOI: 10.1021/bi052543x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monovalent Anions on a Temperature-Dependent Heat Capacity Change for Escherichia coli SSB Tetramer Binding to Single-Stranded DNA

Abstract: We have previously shown that the linkage of temperature-dependent protonation and DNA base unstacking equilibria contribute significantly to both the negative enthalpy change (ΔH obs ) and the negative heat capacity change (ΔC p,obs ) for E. coli SSB homotetramer binding to single stranded (ss) DNA. Using isothermal titration calorimetry we have now examined ΔH obs over a much wider temperature range (5°C to 60°C) and as a function of monovalent salt concentration and type for SSB binding to (dT) 70 under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 78 publications
8
68
0
1
Order By: Relevance
“…Bio-5-AMP binding to the W223A variant exhibits a nonlinear dependence of binding enthalpy on temperature. Although this phenomenology has been observed in other systems, the explanation for the observation in this instance is beyond the scope of this work (30)(31)(32)(33). Partial proteolysis with subtilisin provides a low-resolution measure of the ligand-induced folding of the ABL with bio-5'-AMP binding to wild type BirA resulting in a 6.5-fold decrease in the pseudo-first order cleavage rate.…”
Section: Discussionmentioning
confidence: 63%
“…Bio-5-AMP binding to the W223A variant exhibits a nonlinear dependence of binding enthalpy on temperature. Although this phenomenology has been observed in other systems, the explanation for the observation in this instance is beyond the scope of this work (30)(31)(32)(33). Partial proteolysis with subtilisin provides a low-resolution measure of the ligand-induced folding of the ABL with bio-5'-AMP binding to wild type BirA resulting in a 6.5-fold decrease in the pseudo-first order cleavage rate.…”
Section: Discussionmentioning
confidence: 63%
“…However, the negative heat capacity change associated with the formation of specific protein-DNA complexes could not be completely explained by taking into account only hydration effects [14,17,18]. Other contributions, like the conformational changes of both proteins and nucleic acids accounting for 20% of the total ΔC p [69-72], the modification of the protonation state of the interacting residues [73] and counterion release [74], have been considered. In particular, even if ion release was generally considered to be favorable for complex formation, several studies demonstrated that the negative contribution from ion-molecule electrostatics, rather than the positive entropy given by the ion reorganization, dominates the salt-dependent solvation effects [36,37].…”
Section: Resultsmentioning
confidence: 99%
“…The complexes between SSBs and ssDNA are often very thermodynamically stable (11,12), and their binding relies on the electrostatic interactions between the negatively charged phosphates of the ssDNA and the complementary positively charged residues [lysine (K), arginine (R), or histidine] of the SSBs. The same electrostatic attraction is also required for protein binding to dsDNA (13), with SSBs differentiating ssDNA from its dsDNA competitor on the basis of the intrinsic properties of each, in that dsDNA is significantly less flexible in regards to the spacing and positioning of its negative charges than ssDNA.…”
mentioning
confidence: 99%